Making of MSME Website Design as a Means of Digital Marketing in Tangerang Regency - Tisa Putrinda; Satria Noer Widjanarko; Iwan Zahar (Asian Journal of Community Services, 2022)
In the era of digital transformation, information and communication technology is increasingly advanced, therefore the role of the website in a Micro, Small and Medium Enterprises business is important. The existence of a quality website design in addition to increasing the reputation and trust of consumers is also an effective and efficient marketing tool methods. Based on interviews results that have been carried out at the Habbani Boutique in Tangerang Regency, a modern and professional website design is made to improve marketing and to attract consumers broadly. The observation method is used by visiting the Habbani boutique directly to find out the product to be marketed. The results of this activity are in the form of website design https://butikhabbani.com/.